Fresno Merced Counties Legal Services Staff Party - Watkins, Howard::::::::: (1981)
Mary Ludy, Elaine Harris, Scott Williams, Marilyn Williams, Faheem Hameed, Kathy Reilley; Leroy Cordova and Darci Reid looking at round tray